2012
DOI: 10.1155/2012/167021
|View full text |Cite
|
Sign up to set email alerts
|

The Height Gain in Scoliotic Deformity Correction: Assessed by New Predictive Formula

Abstract: Height gain after scoliosis correction is of a special interest for the patient and family. Ylikoski was the first to suggest a formula predicting height loss in untreated scoliotic patients. Stokes has recently suggested a new formula by using Cobb angle to determine height loss in idiopathic curves. We hypothesized that new additional variables to Cobb angle such as apical vertebral translation (AVT), number of instrumented segments (N), and disc heights may increase the accuracy of predicted height gain. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 11 publications
2
35
1
Order By: Relevance
“…Comparison of the Patient #24 and the Patient #29 confirmed the hypothesis stated by Sarlak et al that using the Cobb angle only for predicting the loss of body height associated with scoliosis may be inaccurate [12]. Two patients with similar curve pattern and Cobb angle values but with the difference in trunk height of 70 mm revealed to have similar loss of height due to their curves calculated by the four analyzed methods.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Comparison of the Patient #24 and the Patient #29 confirmed the hypothesis stated by Sarlak et al that using the Cobb angle only for predicting the loss of body height associated with scoliosis may be inaccurate [12]. Two patients with similar curve pattern and Cobb angle values but with the difference in trunk height of 70 mm revealed to have similar loss of height due to their curves calculated by the four analyzed methods.…”
Section: Discussionsupporting
confidence: 73%
“…All methods employ sophisticated mathematical formulas which make their use in everyday clinical practice cumbersome. Potential for inaccuracy of the methods has been reported, because none of them consider the actual height of the subject with scoliosis [12]. In spite of this hypothesized limitation the methods are being used to calculate BMI or VC of patients with scoliosis [2,5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to identify the underlying factors that could affect the surgical spinal height gain. Significant correlation between correction of the Cobb angle and the increase in spinal longitudinal length was recognized in previous studies 4 5 6 7 . However, controversies still exist concerning the influence of sagittal profile 5 6 , as well as other features such as the length of the curve, number of instrumented vertebrae and curve pattern.…”
mentioning
confidence: 70%
“…As for the sagittal profile, Sarlak and Watanabe’s studies were limited by the fact that the average changes in kyphosis were relatively small 4 7 . Spencer’s study 6 confirmed that changes in kyphosis and lordosis were small and were non-significant predictors of height gain.…”
Section: Discussionmentioning
confidence: 99%
“…Several formulas have been proposed by various authors to determine the increase in height after scoliosis correction. [6][7][8][9] However, these formulas are based on a combination of preoperative and post-operative radiological parameters. Using these formulas, the increase in height could only be determined after the surgery.…”
Section: Introductionmentioning
confidence: 99%